Pengaruh Model Pembelajaran Assure dan Pengetahuan Awal Terhadap Hasil Belajar IPA-Fisika Siswa Kelas Viii SMPN 22 Mataram - Haerul Muammar; Ahmad Harjono; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This is an experimental research. This research aim to examine the effect of ASSURE learning model and prior knowledge on science learning outcome in class VIII of SMPN 22 Mataram. The population is entire students in class VIII SMPN 22 Mataram with VIIIB as experiment class and VIIIC as control class. Both divided into high and low prior knowldege group. This research use factorial design 2x2. Hypothesis test use two ways anava. We got that (1) learning model take significant effect on learning outcome that ASSURE model get higher score than konventional model, (2) prior knowledge take significant effect on learning out come that higher prior knowledge get higher score than the low one, and (3) there is no interaction between learning model and prior knowledge on learning outcome. N-Gain test shown that high prior knowledge of ASSURE class get most improvement result and low pior knowledge of conventional class get worst. It is better to continue this ASSURE learning model in research using another student characterictic analyze. High prior knowledge experiment class get improvement result in all sub-chapter. Low prior knowledge experiment class and high prior knowledge control class get most improvement in wave characteristic. Low prior knowledge control class get most improvement in vibration characteristic.